"Negativibacillus massiliensis" gen. nov., sp. nov., isolated from human left colon. (May 2017) - Ricaboni, D.; Mailhe, M.; Vitton, V.; Andrieu, C.; Fournier, P.-E.; Raoult, D.
Abstract: We report here the main characteristics of "Negativibacillus massiliensis" strain Marseille-P3213 T, isolated from a human left-colon wash sample.